Directing Human Embryonic Stem Cells towards Functional Endothelial Cells Easily and without Purification - Gil, Chang-Hyun; Ki, Byeong-Seong; Seo, Joseph; Choi, Jong-Jin; Kim, Hana; Kim, In-Gul; Jung, A-Ra; Lee, Won-Young; Choi, Youngsok; Park, Kwideok; Moon, Sung-Hwan; Chung, Hyung-Min (KOREAN TISSUE ENGINEERING REGENERATIVE MEDICINE SOC, 2016)
Hemangioblasts or blood islands only arise in early development thereby the sources to obtain these bi-potential cells are limited. While previous studies have isolated both lineages in vitro through the hemangioblast, derivation efficiency was rather low due to cellular damage attributed by enzyme usage and fluorescent activated cell sorting (FACS). This study focused on avoiding the use of damaging factors in the derivation of endothelial cells (ECs). Single cell H9-human embryonic stem cells (hESCs) were obtained by using a mild dissociation protocol then human embryoid body (hEB) formation was performed under hemangioblast differentiation conditions. The hEBs were subjected to a two-stage cytokine treatment procedure. Subsequent culture of the adhesive cells in day 4 hEBs gave arise to a seemingly pure population of ECs. The hESC-derived ECs were characterized by identifying signature endothelial gene and protein markers as well as testing for in vitro functionality. Furthermore, in vivo functionality was also confirmed by transplanting the cells in hindlimb ischemic murine models. We demonstrate that the genetic change required for EC derivation precedes blast colony formation. Furthermore, cell damage was prevented by abating enzyme usage and FACS, resulting in a high yield of ECs upon adhesion. Under this method, confluent cultures of ECs were obtainable 4 days after hEB formation which is significantly faster than previous protocols.